2009
DOI: 10.1007/s11948-009-9149-y
|View full text |Cite
|
Sign up to set email alerts
|

A Rhetorical Analysis of Apologies for Scientific Misconduct: Do They Really Mean It?

Abstract: Since published acknowledgements of scientific misconduct are a species of image restoration, common strategies for responding publicly to accusations can be expected: from sincere apologies to ritualistic apologies. This study is a rhetorical examination of these strategies as they are reflected in choices in language: it compares the published retractions and letters of apology with the letters that charge misconduct. The letters are examined for any shifts in language between the charge of misconduct and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 23 publications
(22 reference statements)
0
7
0
Order By: Relevance
“…Authors are consulted regarding the wording of a retraction, but final decisions are at the discretion of the journal. Some journals appear to give authors considerable latitude in wording a retraction notice (23), but this is probably inadvisable (81). The bloggers at Retraction Watch have advocated transparency in retraction notices (59).…”
mentioning
confidence: 99%
“…Authors are consulted regarding the wording of a retraction, but final decisions are at the discretion of the journal. Some journals appear to give authors considerable latitude in wording a retraction notice (23), but this is probably inadvisable (81). The bloggers at Retraction Watch have advocated transparency in retraction notices (59).…”
mentioning
confidence: 99%
“…Souder [54] provides a linguistic comparison of several letters of apology with the official charges of wrongdoing and concludes, perhaps not surprisingly, that “…published acknowledgments of scientific misconduct seem to minimize culpability by means of the strategic use of language…” . For example, in a 1999 New York Times article on the Fiddes case it was noted that: “… in interviews with the Government after he agreed to plead guilty, Dr. Fiddes portrayed himself as a man trapped by the dishonesty of others.…”
Section: Why Do They Do It?mentioning
confidence: 99%
“…As Souder points out, such apologies are needed so that the culprit will express contrition, the readers will feel reconciled, the other members of the scientific community will be deterred from similar lapses, and the community's faith in the integrity of the system will be restored. 117 Souder's study of published acknowledgements of scientific misconduct in biomedical research journals showed predictably various levels of sincerity in apologies -from denial to mortification. Redman et al found similarly troubling behavior among researchers who had been less than candid about their misconduct.…”
Section: Post-publicationmentioning
confidence: 99%